Dreaming of a good night's sleep: a quality improvement project on improving length and quality of sleep in hospitals - Arbi Hasanaj; Emma Turner; Matthew Wateridge; Jas Virdee (Future Healthcare Journal)
Introduction: In hospitals, environmental factors, such as noise from alarms, frequent medical checks and disturbances from staff and patients, can cause sleep disturbances.1 Poor sleep in hospital may be linked to delayed recovery and impact the length of stay.2,3 This study examined the implementation and effectiveness of a new structured sleep intervention, termed ‘SLEEP’ (silencing machines, lights off at 11 pm, eye masks, ear plugs and promoting sleep hygiene), to enhance sleep duration and quality. Materials and methods: The study assessed whether structured sleep interventions could increase sleep duration and quality in hospitalised patients. It measured changes in sleep duration before and after intervention, time taken to fall asleep and frequency of nighttime waking.The study was conducted across three hospital wards: surgical, gastro/general medicine and geriatric. Patients were surveyed using online questionnaires about their sleep patterns at three stages: before hospital admission (at home), in hospital before the intervention and in hospital after the intervention. The intervention was rolled out through posters, staff training and the distribution of sleep aids across the three hospital wards. A total of 29 responses were collected across several days on the second cycle of the project, where SLEEP was developed and implemented. Statistical analysis was performed to compare mean sleep duration before and after intervention, with significance set at p <0.05. Results and discussion: Before the intervention, patients’ average sleep duration dropped from 7 h 14 min (SD=1.46) at home to 3 h 50 min (SD=1.87) in the hospital (p <0.05). Following the intervention, sleep duration increased to 5 h 14 min (SD=1.72), an improvement of 1 h and 25 min from pre-intervention figures (p <0.05). An additional finding was that patients fell asleep 33 min faster post intervention compared with pre-intervention. However, frequent awakenings persisted due to noise from staff activities and disruptive patients. Silencing machines was challenging due to medical needs, and no significant change was observed in this practice following this intervention. There was mixed feedback on sleep aids; earplugs effectively blocked noise but were uncomfortable, while eye masks were of poor quality. Despite these limitations, results indicated a positive trend in improving patient sleep duration through structured interventions (Figs 1 and 2). Conclusion: The SLEEP intervention led to a significant increase in patient sleep duration, although challenges remain in fully optimising sleep quality in the hospital setting. Future cycles should explore further strategies to minimise disruptions, improve the comfort of sleep aids and increase staff awareness of sleep-promoting practices to shorten hospital stays and increase patient well-being.